2011
DOI: 10.3892/etm.2011.237
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib and hepatic arterial infusion chemotherapy for unresectable advanced hepatocellular carcinoma: A comparative study

Abstract: Abstract. Sorafenib is a kinase-targeted drug that has high efficacy for advanced hepatocellular carcinoma (HCC). The aim of the present study was to determine whether sorafenib is more effective than hepatic arterial infusion chemotherapy (HAIC) for HCC. Twenty patients treated with sorafenib (sorafenib group) initiated at 800 mg/day and 45 patients treated with HAIC (HAIC group) for unresectable Child-Pugh A advanced HCC were investigated retrospectively. The treatment effect was assessed using the Response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 34 publications
4
25
1
Order By: Relevance
“…Importantly, a recent retrospective study by the same group in Korea compared HAIC and sorafenib in advanced HCC patients with portal vein tumor thrombosis and showed better overall survival (7.1 and 5.5 mo, respectively; P = 0.011) and longer median time to progression (3.3 and 2.1 mo, respectively; P = 0.034) in the HAIC group [75] . These findings are consistent with those of a Japanese study [76] . Although well-designed prospective studies are warranted to confirm these results, HAIC at least appears to be an alternative therapy for patients with portal vein tumor thrombosis when sorafenib is not available or is intolerable.…”
Section: Medical Therapiessupporting
confidence: 83%
“…Importantly, a recent retrospective study by the same group in Korea compared HAIC and sorafenib in advanced HCC patients with portal vein tumor thrombosis and showed better overall survival (7.1 and 5.5 mo, respectively; P = 0.011) and longer median time to progression (3.3 and 2.1 mo, respectively; P = 0.034) in the HAIC group [75] . These findings are consistent with those of a Japanese study [76] . Although well-designed prospective studies are warranted to confirm these results, HAIC at least appears to be an alternative therapy for patients with portal vein tumor thrombosis when sorafenib is not available or is intolerable.…”
Section: Medical Therapiessupporting
confidence: 83%
“…Some studies have suggested that the efficacy of HAIC may not be inferior to that of sorafenib for the treatment of advanced HCC in patients who are not candidates for surgical resection or nonsurgical interventions; however, the survival benefit of HAIC has not been established, since no prospective studies have demonstrated a prolonged survival. To obtain exploratory preliminary data for HAIC with cisplatin or sorafenib in patients without extrahepatic metastasis and who have not responded to prior TACE procedure, we retrospectively investigated the effect of HAIC and sorafenib treatment in HCC patients treated with prior TACE using a propensity score‐based weighting to adjust for selection differences between the two treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…9 Although it is not yet a well-established treatment due to the lack of the evidence from large randomized studies, hepatic arterial infusion chemotherapy (HAIC) which usually involves cisplatin and 5-fluorouracil (5-FU) or intra-arterial 5-FU infusion with systemic interferon (IFN) therapy, has been efficient for patients with advanced HCC and portal vein tumor thrombosis (PVTT) 10,11 and has been chosen as an alternative treatment to sorafenib in Japan and other Asian countries. [12][13][14] Cisplatin, which is prepared for HAIC as a fine powder formulation (IA call; Nippon Kayaku, Tokyo, Japan), was approved in Japan in 2004. This agent is a high-concentration (1.4 mg/mL) aqueous solution of cisplatin, in comparison with conventional cisplatin formulations (0.5 mg/ mL).…”
Section: Introductionmentioning
confidence: 99%
“…Hiramine et al [48] attempted to determine whether sorafenib (n=20) was more effective than HAIC (n=45) for treating HCC. However, sorafenib treatment was discontinued in 19 patients (95%), including 12 who experienced side effects.…”
Section: Haic Versus Sorafenibmentioning
confidence: 99%